The off-campus student teaching program of private teacher colleges in Davao City its organization, administration and supervision - Lozada, Enrique M. 1924- ([Quezon City s.n.], 1967)
This study provides a description of the existing conditions in the organization, administration, and supervision of the off-campus student teaching program of private teacher colleges in Davao City in order to identify the problems encountered in the field and to offer solutions relevant to these aspects.
Thesis (M.Ed.)--University of the Philippines
Keywords: Student teaching -- Davao City